Evaluation of neurological deficiency in rats with cerebral ischaemia following the administration of omega polyunsaturated fatty acids - Bon, Lizaveta; Maksimovich, Nataliya Ye. (Journal of Medical Science, 2021)
Aim. The aim of the study was to assess the degree of neurological deficit in rats with experimental cerebral ischaemia following the administration of omega-3 polyunsaturated fatty acids. Material and Methods. The experiments were conducted on 42 male outbred white rats weighing 260 ± 20 g. The modelling of cerebral ischaemia was performed with intravenous thiopental anaesthesia (40-50 mg / kg), and the research involved models of subtotal, partial and stepwise subtotal cerebral ischaemia. Subtotal cerebral ischaemia (SCI) was modelled by simultaneous ligation of both common carotid arteries (CCA). Partial cerebral ischaemia (PCI) was modelled by ligating one CCA on the right. Stepwise subtotal CI (SSCI) was performed by sequential ligation of both CCA within the intervals of 1 day (subgroup 1), 3 days (subgroup 2), or 7 days (subgroup 3). In order to investigate the effects of omega-3 polyunsaturated fatty acids (ω-3 PUFA), animals with CI were injected intragastrically with the drug "Omegamed" (SCI+ω-3 PUFA) at a dose of 5 g / kg of body weight for the duration of one week. The control group consisted of sham-operated rats of the same sex and weight. Neurological deficits were assessed with regard to the "muscle strength", "swimming test" and "open field" tests after 5-6 hours of the ischaemic period.Results. Following a stepwise bilateral ligation of both common carotid arteries with a 1 day interval, neurological disorders were most prominent, which indicates an aggravation of neurological deficit with a reduction in the time between CCA dressings. In rats with SCI, the changes were more visible than with PCI, although they were less observable than in the group with SCI. The least noticeable changes were noted in the 3rd subgroup (with a 7 day interval between CCA dressings). Research has demonstrated a dependence of the severity of brain damage in SSCI on the interval between the blood supply cessation in both CCA. In the course of a 7 day interval between CCA dressings, the compensatory mechanisms were activated, which prevented the development of morphological changes and neurological deficits. When CCA was ligated within 1 day interval, the degree of neurological deficit was maximal, indicating an insufficient implementation of compensatory mechanisms. In comparison with the control group, the rats of the "SCI+ω3-PUFA" group retained neurological deficit, the muscle strength indicator was decreased by 86% (p
Keywords: cerebral ischaemia; rats; neurological deficiency; omega-3 polyunsaturated fatty acids